2016
DOI: 10.1158/1940-6207.capr-15-0419
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Akt Enhances the Chemopreventive Effects of Topical Rapamycin in Mouse Skin

Abstract: The PI3Kinase/Akt/mTOR pathway has important roles in cancer development for multiple tumor types, including UV-induced non-melanoma skin cancer. Immunosuppressed populations are at increased risk of aggressive cutaneous squamous cell carcinoma (SCC). Individuals who are treated with rapamycin, (sirolimus, a classical mTOR inhibitor) have significantly decreased rates of developing new cutaneous SCCs compared to those that receive traditional immunosuppression. However, systemic rapamycin use can lead to signi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 47 publications
2
28
0
Order By: Relevance
“…We then examined the effect of pharmacological inhibition of TLR4 on UVinduced MAP kinase signaling employing solar-simulated light (SSL). SSL uses a light source which replicates the relative contributions of UVA and UVB found in natural sunlight, as previously published (3,37). We observed that stimulation of p38 MAP kinase phosphorylation in response to SSL was attenuated in the presence of resatorvid (Fig.…”
Section: Genetic or Pharmacological (Resatorvid-based) Inhibition Of supporting
confidence: 78%
See 1 more Smart Citation
“…We then examined the effect of pharmacological inhibition of TLR4 on UVinduced MAP kinase signaling employing solar-simulated light (SSL). SSL uses a light source which replicates the relative contributions of UVA and UVB found in natural sunlight, as previously published (3,37). We observed that stimulation of p38 MAP kinase phosphorylation in response to SSL was attenuated in the presence of resatorvid (Fig.…”
Section: Genetic or Pharmacological (Resatorvid-based) Inhibition Of supporting
confidence: 78%
“…For in vivo exposures, a bank of 6 UVA340 bulbs was utilized within an approved ventilated animal rack. Fluence intensity for both types of bulbs was measured as described previously .…”
Section: Methodsmentioning
confidence: 99%
“…mTOR inhibitors such as rapamycin are currently being used to decrease the risk of CSCC development in immunosuppressed patients that receive traditional immunosuppression [95][96][97]. Combining topical mTOR inhibitors and AKT inhibitors (PHT-427) enhances the chemopreventive effects of rapamycin [98]. Pan-PI3K and selective PI3K inhibitors have been developed to treat other cancers [99].…”
Section: Other Targeted Therapies In Csccmentioning
confidence: 99%
“…In addition, organ-transplant patients who took rapamycin as an immunosuppressive drug had a significant reduction in acquired NMSC when compared to patients taking cyclosporine A [164]. Our lab and others have demonstrated that mTORC1 is required for keratinocyte hyperproliferation in response to tumor promotion in murine skin carcinogenesis models [129, 165]. There is controversy regarding the role of mTORC1 in NMSC tumor initiation.…”
Section: Rtk Activationmentioning
confidence: 99%
“…Studies from our lab showed that treatment with rapamycin or genetic knockdown of the essential mTORC1 scaffolding protein Raptor does not affect cell viability or apoptosis following exposure to UVB in spontaneously immortalized human keratinocytes (HaCaT cells) or mouse primary keratinocytes [129, 145]. In contrast, a recent report by Bowden and colleagues showed that rapamycin treatment did increase UVR-induced keratinocyte cell death in mice [165]. The differing results seen in these studies are likely due to the differences in both model systems and UVR-dosages used.…”
Section: Rtk Activationmentioning
confidence: 99%